The political and economic conditions in the Emirate of Eastern Jordan1921- 1939 (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The region of Eastern Jordan was part of the Levant, and it had been under Ottoman rule since 1516. and It continued under their rule four centuries. And the fact that This area is located on the Shami pilgrimage road heading  to Makkah. Gave it great importance, which prompted the Ottoman Empire to protect This road and the establishment of centers to protect it and to secure the various requirements of pilgrims in terms of water food and other services, what  increased the importance of East Jordan region is the extension of the Hijaz railway from Damascus to the Hijaz, crossing the eastern Jordan region from the north to the south , and the opening of this line took place in 1908. East of Jordan in the Council of the Ottoman envoys had one envoy from Karak, and when the Great Arab Revolution joined the tribes of East Jordan to the forces of Prince Faisal bin Al -Hussein heading to Damascus, to liberate the Levant from the Ottomans.